Gambaran Perilaku Autonomy Support pada Guru di Sekolah MTs X Jatinangor - Laras Yuliansyah; Surya Cahyadi; Erna Susiati (Provitae: Jurnal Psikologi Pendidikan, 2020)
A teacher’s motivating style toward students is an important educational construct. Teacher-provided autonomy support benefits students and teachers themselves. Students who receive autonomy support from their teachers experience greater autonomus motivation and classroom engagement. For teachers, they experience greater teaching efficacy and vitality during teaching. Autonomy support is the interpersonal sentiment and behavior the teachers provide to identify, nurture, and develop students’ inner motivational resources. The purspose of this study is to obtain an overview of autonomy support in teachers of Madrasah Tsanawiyah (MTs) X Jatinangor. The design of this study is explanatory sequential mixed method. The quantitative data were obtained from 37 teachers of MTs X Jatinangor who completed The Problems in School Questionnaire (PIS) to explain teacher’s orientation toward motivating students. The sampling methods in quantitative approach is saturated sampling. The qualitative data were obtained from interview with 6 teachers of MTs X Jatinangor regarding teacher’s motivating style and the causes influence teacher’s controlling style during learning activities. The sampling methods in qualitative approach is purposive sampling. The results showed that 36 teachers (97,3%) have moderately autonomy supportive orientation and 1 teacher (3,7%) has highly autonomy supportive orientation. Therefore, most of the teachers in school MTs X Jatinangor implement autonomy support and controlling motivating style during class. The causes of the teacher’s controlling style are that teachers harbor the dual burdens of responsibility and occupy an inherently powerful social role.